Implementasi Manajemen Berbasis Sekolah (MBS) dalam Meningkatkan Mutu Lembaga Pendidikan di Madrasah Tsanawiah (MTs) Al-Hidayah Cibadak-Banten - Wiwin Nurhanah Wiwin Nurhanah (E-Jurnal Aksioma Ad-Diniyyah : The Indonesian Journal of Islamic Studies, 2016)
Implementation of education in the era of regional autonomy especially madrasah not experiencing autonomy as well as schools under the Ministry of National Education. Because madrassas are under the auspices of the Ministry of Religious Affairs, and the Department of Religion is an Un-Autonomous Department. So the madrasas have structural constraints and are in problematic situations. The purpose of this study is to know whether Implementation of School Based Management Able to Improve the Quality of Education Institution in MTs Al-Hidayah Cibadak. The method used is qualitative research methods with research procedures that produce descriptive data in the form of written words and oral from the people and observed behavior. The results of this study were 1) In the beginning before MBS was applied in MTs Al Hidayah, the curriculum used was KTSP. But the implementation has not been implemented properly because the school has not understood the importance of the curriculum. However, after the implementation of SBM, curriculum management can work well and smoothly because teachers understand the importance of the curriculum and know how to apply it. 2) Prior to the implementation of SBM, the number of educators reached 14 people but most of them have not the status of S-1 education. However, after the implementation of MBS the number of educators increased to 17 people and has the status of S-1 education is only a few teachers who have not been because they are still studying. 3) Before the implementation of SBM, the number of students is only 9 people. However, after the application of MBS the number of students increased drastically to 143 students by 2016. In addition, the number of student activities held. 4) Prior to the implementation of SBM, the existing finance in MTs Al Hidayah only came from private foundations. However, after the implementation of SBM get assistance from the government in the form of BOS. Although the funds are not sufficient, but it is very helpful school finance. 5) Prior to the implementation of SBM, the existing suggestions and infrastructure included only 2 classrooms, 1 tolilet, and school cafeteria. However, after the application of MBS, the facilities and infrastructures increased to 5 (five) units of study, 1 (one) office / teacher room, 1 unit of headmaster room, 1 (one) multipurpose hall unit, 1 school cafeteria unit, 2 (two) student toilet units, 2 (two) teacher restroom units, 1 (unit) school equipment warehouse, 1 (one) school kitchen unit, volleyball field, basketball court and soccer field. 6) Before and after the MBS was implemented in MTs Al Hidayah Cibadak, the relationship between the school and the community never changed, always prioritizes cooperation and always supports school programs.Penyelenggaraan pendidikan di era otonomi daerah khususnya madrasah tidak mengalami otonomi seperti halnya sekolah-sekolah di bawah Departemen Pendidikan Nasional. Karena madrasah berada dibawah naungan Departemen Agama, dan Departemen Agama adalah Departemen yang tidak diotonomikan. Sehingga madrasah mengalami kendala struktural dan berada dalam situasi problematika. Tujuan penelitian ini adalah untuk mengetahui Apakah Implementasi Manajemen Berbasis Sekolah Mampu Meningkatkan Mutu Lembaga Pendidikan di MTs Al- Hidayah Cibadak. Metode yang digunakan adalah  metode penelitian kualitatif dengan prosedur penelitian yang menghasilkan data deskriftif berupa kata-kata tertulis maupun lisan dari orang-orang dan prilaku yang diamati. Hasil dalam penelitian ini adalah 1) Pada awalnya sebelum MBS diterapkan di MTs Al Hidayah, kurikulum yang digunakan adalah KTSP. Tetapi pada pelaksanaannya belum diterapkan dengan baik karena pihak sekolah belum memahami pentingnya kurikulum. Tetapi, setelah diterapkannya MBS manajemen kurikulum dapat berjalan dengan baik dan lancar karena para guru sudah memahami pentingnya kurikulum dan tahu cara penerapannya. 2) Sebelum diterapkannya MBS, jumlah tenaga pendidik mencapai 14 orang tetapi kebanyakn belum berstatus pendidikan S-1. Tetapi, setelah diterapkannya MBS jumlah tenaga pendidik bertambah menjadi 17 orang dan sudah berstatus pendidikan S-1 hanya beberapa guru saja yang belum karena masih menempuh pendidikannya. 3) Sebelum diterapkannya MBS, jumlah siswa hanya 9 orang. Tetapi, setelah diterapkannya MBS jumlah siswa meningkat drastic menjadi 143 siswa pada tahun 2016 ini. Selain itu, banyaknya kegiatan-kegiatan siswa yang diselenggarakan. 4) Sebelum diterapkannya MBS, keuangan yang ada di MTs Al Hidayah hanya bersumber dari yayasan pribadi. Tetapi, setelah diterapkannya MBS mendapatkan bantuan dari pemerintah berupa BOS. Walaupun dana tersebut tidak mencukupi sepenuhnya, tetapi sangat membantu keuangan sekolah. 5) Sebelum diterapkannya MBS, saran dan prasarana yang ada hanya meliputi 2 ruang kelas, 1 tolilet, dan kantin sekolah. Tetapi, setelah diterapkannya MBS sarana dan prasarana tersebut bertambah menjadi 5 (lima) unit ruang belajar, 1 (satu) unit ruangan kantor/ruang guru, 1 (satu) unit ruang kepala madrasah,  1 (satu) unit ruangan serbaguna (aula), 1 (satu) unit kantin sekolah, 2 (dua) unit toilet murid, 2 (dua) unit toilet guru, 1 (unit) gudang peralatan sekolah, 1 (satu) unit dapur sekolah, lapangan volley, lapangan basket dan lapangan bola. 6) Sebelum dan setelah MBS diterapkan di MTs Al Hidayah Cibadak, hubungan antara sekolah dengan masyarakat tidak pernah berubah, selalu mengutamakan kerjasama dan selalu mendukung program-program sekolah.